Effects of emotional acceptance and rumination on media-induced body dissatisfaction in anorexia and bulimia nervosa. (November 2016) - Naumann, Eva; Tuschen-Caffier, Brunna; Voderholzer, Ulrich; Schäfer, Johanna; Svaldi, Jennifer
Abstract: Introduction: Body dissatisfaction is an important risk and maintaining factor for eating disorders. The aim of the present study was to experimentally test the effects of two emotion regulation strategies - acceptance and rumination - on media-induced body dissatisfaction in eating disorders. Method: After watching pictures of thin models, women with anorexia nervosa (AN; n  = 39) and bulimia nervosa (BN; n  = 39) were encouraged to either use emotional acceptance or rumination to cope with their feelings. Body dissatisfaction and mood were repeatedly assessed. Results: Acceptance significantly improved body dissatisfaction in women with BN. Rumination led to a significant increase of body dissatisfaction in both eating disorder groups. Results were independent from mood changes. Discussion: Findings highlight the importance ruminative thinking may have in the aggravation of dissatisfaction with the own body in AN and BN. Results suggest that emotional acceptance is a useful strategy to regulate body dissatisfaction after exposure to thin-ideal media in BN.